The Effect of Intranasal Splint on Prevention of Adhesion After Septoplasty - Farhad Jalil Khayat; Abdulmajeed Yaseen (Diyala Journal of Medicine, 2019)
Background: Intranasal adhesion is one of the common complications following nasal surgeries. Using nasal splint during the surgery is one of the methods for prevention of this complication.